Educação cívica: a história de um conceito no Brasil Republicano - Guilherme, Karina Clécia da Silva (2024)
Discussions around civic education, nationalism, and national symbols periodically return to the national agenda, mobilizing researchers and public policies. These dialogues address a set of practices aimed at preparing citizens to participate actively in democratic society, teaching political knowledge, rights, ethical, moral, and civic values. The research aimed to analyze and understand the historical process of constructing the concept of "civic education" in three distinct periods: First Republic (1889-1930), Estado Novo (1937-1945), and Civil-Military Dictatorship (1964-1985), each triggered by the following events respectively: Proclamation of the Republic (1889), Estado Novo Coup (1937), and Civil-Military Dictatorship Coup (1964). For a broader analysis, the investigation considered temporalities before and after these events. The research contributes to the field of Conceptual History. The theoretical-methodological foundations include the concepts of "temporality," "concept," and "event" as theorized by Koselleck (1992; 2006; 2014). Furthermore, to analyze how the concept of civic education was approached over time, texts such as textbooks and supplementary materials were used, available at the Textbook Library (BLD) of USP, the Center for Documentation and Historical Research (CDPH) of Unitau, and the Brasiliana Guita e José Mindlin Library (BBM), as well as periodicals from the Brazilian Digital Newspaper Library of the National Library. In this sense, the analysis of texts published in various sources by different authors in different places facilitated the understanding of the meanings attributed to the Concept of Civic Education in Brazil, considering the proposed temporal framework. The results indicate that the concept of civic education underwent significant changes and continuities over the periods studied. During the First Republic, the concept focused on values such as patriotism, rights, duties, and order. In the Estado Novo period, these values were reinterpreted to reinforce the nationalist and authoritarian ideology of the Vargas government. During the Civil-Military Dictatorship, the concept incorporated elements of national security and anti-communism, reflecting the repression and control of the military regime. Each period adapted the concept to its political and social needs, demonstrating its dynamic and contextual nature. Nevertheless, certain ideas persisted throughout the studied periods and throughout Brazilian civic education history. These enduring values include patriotism, order, discipline, moral, ethical, and civic values, and the rights and duties of citizens